The Extraction and Impact of Essential Oils on Bioactive Films and Food Preservation, with Emphasis on Antioxidant and Antibacterial Activities—A Review - Sohail Khan; Abdullah A. A. Abdo; Ying Shu; Zhisheng Zhang; Tieqiang Liang (Foods, 2023)
Essential oils, consisting of volatile compounds, are derived from various plant parts and possess antibacterial and antioxidant properties. Certain essential oils are utilized for medicinal purposes and can serve as natural preservatives in food products, replacing synthetic ones. This review describes how essential oils can promote the performance of bioactive films and preserve food through their antioxidant and antibacterial properties. Further, this article emphasizes the antibacterial efficacy of essential oil composite films for food preservation and analyzes their manufacturing processes. These films could be an attractive delivery strategy for improving phenolic stability in foods and the shelf-life of consumable food items. Moreover, this article presents an overview of current knowledge of the extraction of essential oils, their effects on bioactive films and food preservation, as well as the benefits and drawbacks of using them to preserve food products.